2022
DOI: 10.1503/jpn.210180
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the neurobiological basis of anhedonia in major depressive disorder — evidence for reduced neural activation during reward and loss processing

Abstract: Background: Anhedonia is a key symptom of major depressive disorder (MDD). Anhedonia is associated with aberrant reward processing, but whether it might interfere similarly with the neural processing of aversive stimuli, such as monetary loss, remains unknown. We aimed to investigate potential associations between anhedonia and neural response during reward and loss processing in patients with MDD. Methods: We investigated blood-oxygen-level-dependent response in the orbitofrontal cortex, cingulate cortex, ins… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
0
0
Order By: Relevance
“…Some individuals with major depression or schizophrenia are reported to have symptoms of consummatory or true anhedonia, meaning inability to experience pleasure, while others may have a more selective avolition or anticipatory anhedonia, meaning loss of motivational 'wanting' for life rewards even if hedonic reactivity remains intact (70)(71)(72)(73). A recent study in humans found that patients with major depressive disorder with anhedonia had blunted fMRI BOLD responses in OFC and insula during a monetary gain/ loss task, suggesting that in humans these cortical regions may contribute to hedonic dysfunction (74). Whether activation of the cortical suppressive 'hedonic coldstrip' described here contributes to reduced pleasure in true anhedonia, or whether promoting activity in hedonic hotspots could reverse such hedonic deficits remain open questions that could be addressed by future clinical research.…”
Section: Discussionmentioning
confidence: 99%
“…Some individuals with major depression or schizophrenia are reported to have symptoms of consummatory or true anhedonia, meaning inability to experience pleasure, while others may have a more selective avolition or anticipatory anhedonia, meaning loss of motivational 'wanting' for life rewards even if hedonic reactivity remains intact (70)(71)(72)(73). A recent study in humans found that patients with major depressive disorder with anhedonia had blunted fMRI BOLD responses in OFC and insula during a monetary gain/ loss task, suggesting that in humans these cortical regions may contribute to hedonic dysfunction (74). Whether activation of the cortical suppressive 'hedonic coldstrip' described here contributes to reduced pleasure in true anhedonia, or whether promoting activity in hedonic hotspots could reverse such hedonic deficits remain open questions that could be addressed by future clinical research.…”
Section: Discussionmentioning
confidence: 99%